2020
DOI: 10.1097/md.0000000000022746
|View full text |Cite
|
Sign up to set email alerts
|

MR prediction of pathologic complete response and early-stage rectal cancer after neoadjuvant chemoradiation in patients with clinical T1/T2 rectal cancer for organ saving strategy

Abstract: To evaluate the ability of magnetic resonance imaging (MRI) to predict pathologic complete response (pCR) after neoadjuvant chemoradiation therapy (CRT) in patients with clinical T1/T2 rectal cancer to indicate candidates for organ-saving strategies. Between 2012 and 2016, 38 patients with clinical T1/T2 rectal cancer received neoadjuvant CRT. Radiologic complete response (rCR) was assigned when dense fibrotic tissue without tumor signal intensity was observed on post-CRT MRI. Surgical pathologic as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Unfortunately, CRM status on MRIs after CRT (before surgery) had a lack of statistical significance for survival in our study (p=0.07 in RFS). As a related study, Bae et al 19 reported the usefulness of follow-up MRI for the prediction of pCR after neoadjuvant CRT in patients with clinical T1/T2 rectal cancer. In addition, as studies on radionomic analysis to improve the prediction of pCR have recently been reported, further imaging methods may help select high-risk patients.…”
Section: Discussionmentioning
confidence: 95%
“…Unfortunately, CRM status on MRIs after CRT (before surgery) had a lack of statistical significance for survival in our study (p=0.07 in RFS). As a related study, Bae et al 19 reported the usefulness of follow-up MRI for the prediction of pCR after neoadjuvant CRT in patients with clinical T1/T2 rectal cancer. In addition, as studies on radionomic analysis to improve the prediction of pCR have recently been reported, further imaging methods may help select high-risk patients.…”
Section: Discussionmentioning
confidence: 95%
“…Despite many studies favoring the ability of MRI to depict pre- and post-PCRT rectal cancer status [ 20 , 21 ], depending on MRI for choosing surgical strategies in post-PCRT patients raises concerns. The mrTRG has recently been widely used to evaluate clinical tumor response to chemoradiotherapy in patients with LARC treated with PCRT.…”
Section: Discussionmentioning
confidence: 99%